An assessment of a technique to derive stream longitudinal profiles: a GIS approach - Moolman, Juanita (University of the Free State, 2012)
The South African Water Act (Act 36 of 1998) (NWA, 1998) requires the calculation of the amount of water required for ecological sustainability in aquatic systems. Part of this process is the classification of slopes according to geomorphological class, which in turn requires, inter alia, the derivation of river longitudinal profiles from which to calculate these slopes. This has prompted the need to develop a method for obtaining these slopes that is fast and repeatable, and can be applied at both a national as well as sub-catchment level. Input data sets are required that are consistently available at a national as well as a sub-catchment level. This study will assess the results of using a semi-automated GIS procedure to derive longitudinal river profiles and slopes, based on nationally available data sets, in a test catchment. In recent years the use of Digital Elevation Models (DEMs) is replacing contour lines on topographic map sheets as the source of elevation inputs required to construct longitudinal profiles. The main question put forward is: can river longitudinal profiles and slopes generated from a DEM and based on 1:500 000 mapped river lines adjusted to within 50m of 1:50 000 mapped river lines, be used as effectively as river longitudinal profiles extracted from 1:50 000 mapped contours and based on 1:50 000 mapped rivers lines? Primary catchment X, situated in eastern South Africa, is used as the test area for this study. River channels in this catchment represent a range of slopes, from steep mountains streams to flat lowland rivers. The assessment is undertaken on 109 rivers identified at 1:500 000 scale in primary catchment X. These river lines are based on those originally scanned and vectorised from 1:500 000 topographic map sheets. These lines are available at a national level, have been connected to form a continuous network and horizontally adjusted to improve locational accuracy to within 50m of the river lines on 1:50 000 topographic map sheets (DWAF, 2003; DWAF, 2006). Profile elevation values extracted from three medium to low resolution Digital Elevation Models are examined in this study. This study compares slopes based on the elevation values extracted from DEMs according to adjusted 1:500 000 river lines, to those extracted from contour lines on 1:50 000 topographic map sheets according to 1:50 000 scanned river lines. These input data sets and any limitations associated with them are discussed. A semi-automated method used to extract and compile the elevation and distance values required to construct longitudinal profiles and the statistical tests and procedures used to compare elevation and slope values, are also described. Comparisons are formed around two reference scenarios. In the first elevations are extracted at the intersections of river lines with 1:50 000 scanned contour lines. The second reference scenario uses these same derived longitudinal profiles, but divided into five sets of equal horizontal intervals: 100m, 200m, 300m, 400m and 500m. Finally, the conclusions that can be drawn form these results, together with any recommendations for either improving or even replacing the data sets and methods described in this study, are presented. It is found that, that when comparing slopes derived from 1:50 000 contour line elevations to those based on DEM elevations, steep slopes tend to be more underestimated by the DEM than flatter slopes. More than 90% of profiles based on contour intervals and more than 90% of slopes derived at 500m horizontal distance intervals show no significant difference between slopes. It is finally suggested that the adjusted 1:500 000 river lines available from DWA (DWAF, 2003; DWAF 2006) combined with elevations from medium to low resolution DEMs can be used as a substitute for 1:50 000 river line and contour linebased profiles. It is also suggested that the automated GIS procedure used to extract and combine these values can be applied in other areas where the 1:500 000 river lines and medium to low resolution DEMs are available.

Die Suid-Afrikaanse Nasionale Waterwet (Wet 36 van 1998) vereis die berekening van waterbehoeftes vir ekologiese volhoubaarheid in akwatiese stelsels. Hierdie sluit in die klassifikasie van rivierhellings in terme van geomorfologiese klasse, en dus ook die ontrekking van rivier lengteprofiele as basis vir die berekining van hierdie hellings. Dit is nodig om ‘n vinnige en herhaalbare metode te ontwikkel wat rivierhellings op ‘n nasionale sowel as opvanggebied skaal, kan voorsien. Data vir die metode moet dus ook op ‘n nasionale sowel as opvanggebied skaal beskikbaar wees. Hierdie studie ondersoek resulte van ‘n semioutomatiese GIS (Geografiese Inligtingstelsel) metode om rivier lengteprofiele en hellings te ontrek, in ‘n toetsopvanggebied. Data wat gebruik word moet ook beskikbaar wees op ‘n nasionale vlak, Die gebruik van digitale hoogtemodelle (DHM) vervang al hoe meer kontoerlyne op topografiese kaarte as ‘n bron van hoogtewaardes om lengteprofiele saam te stel. In die studie word die primere vraag: Kan lengteprofiele en hellings gebaseer op ‘n DHM en op gekarteerde rivierlyne op `n 1:500 000 skaal, en aangepas tot binne 50m van 1:50 000 gekarteerde lyne, vergelyk word met dié wat gebaseer is op 1:50 000 gekarteerde kontoerlyne en rivierlyne, ondersoek. Die studiegebied is Primêre dreineringsbekken X in Mpumalaga (oostelike Suid-Afrika). Riviere in hierdie opvanggebied verteenwoordig ‘n verskeidenheid van hellings, vanaf steil bergstrome na die vlaktes van die Laeveld. Teen ‘n skaal van 1:500 000 behels die dreineringsbekken 109 rivierlyne, gebaseer op 1:500 000 geskandeerde en versyferde topografiese kaarte. Die lyne is nasionaal beskikbaar, vorm ‘n ongebroke lynnetwerk en is horisontaal aangepas tot binne 50m van die riviere op 1:50 000 topografiese kaarte (DWAF, 2003; DWAF, 2006). Hoogtewaardes vir vergelyking is onttrek van drie medium na lae resolusie digitale hoogtemodelle. Helllings onttrek van die DHM volgens die aangepaste 1:500 000 rivierlyne is vergelyk met dié onttrek van kontoerlyne en riviere op 1:50 000 topografiese kaarte. Hierdie datastelle sowel as hulle beperkings is bespreek. Die semi-outomatiese metode wat hoogte en afstand waardes onttrek, sowel as die statistiese prosedures wat gebruik word om vergelykings te maak, is ook bespreek. Vergelykings is gemaak op die basis van twee scenarios. In die eerste scenario is hoogtes vir lengteprofiele ontrek op 1:50 000 geskandeerde rivier en kontoerlynkruisings. In die tweede scenario is hierdie lengteprofiele ingedeel in vyf stelle horisontale afstande: 100m, 200m, 300m, 400m and 500m. Laastens word die gevolgtrekkings en enige aanbevelings wat voortspruit uit die studie, bespreek. Die bevinding is dat as hellings wat gebaseer is op 1:50 000 kontoerlyne vergelyk word met dié wat gebaseer is op DHM hoogtes, is steil hellings meer onderskat deur die DHM as meer gelyk hellings. Meer as 90% van die profiele gebaseer op die afstande tussen kontoerlyne en meer as 90% van dié gebaseer op 500m horisontale afstande het geen betekenisvolle verskille tussen hellings nie. Dit is voorgestel dat lengteprofiele gebaseer op 1:50 000 rivier en kontoerlyne, vervang kan word met lengteprofiele gebaseer op die aangepaste 1:500 000 riverlyne beskikbaar vanaf DWA (DWAF, 2003; DWAF 2006) en gekombineer met hoogtes onttrek van medium na lae resolusie digitale hoogtemodelle. Dit is ook voorgestel dat die outomatiese GIS prosedure wat benut word om waardes te onttrek en kombineer ook gebruik kan word in ander dele waar 1:500 000 riverlyne en ‘n medium tot lae resolusie DHM beskikbaar is.
Dissertation (M.Sc. (Geography))--University of the Free State, 2012
Keywords: Geodatabases; Rivers -- Longitudinal studies; Digital evaluation models; Topographic map; SRTM; Slope; River longitudinal profile; GIS; Contour; Elevation